Advanced modelling of porous screens in aerodynamic diffusers using variable resistance factors - Janse van Rensburg, Jacobus Johannes (My University, 2014)
Strict emission legislation has forced industry in general to seriously consider the negative impact it has on the environment, specifically concerning emissions from burning fossil fuel into the atmosphere. In cases where emission levels exceed the allowable limit, companies are forced to operate at lower operating conditions and these load losses can result in a significant loss of revenue. This has forced companies to improve their ash filtering capabilities by optimising electrostatic precipitation systems. One of the main factors impacting on the efficiency of such a system is the distribution of the flow across the collection plates. The design of the inlet diffuser plays a major role in the ultimate distribution of the flow through the precipitator. Porous screens are positioned in the diffuser in order to distribute the flow across the total flow area with the aim to achieve a uniform distribution of the flow. CFD is widely used in industry to simulate the flow through precipitators in order to optimise the flow distribution and thus increase the efficiency of the system. It was found however that the current methods used to simulate these screens in CFD models were not well researched and employed fixed resistance values that could not reliably compensate for changes in the resistance coefficient due to a change in the angle of incidence. This study investigates advanced numerical methods for the simulation of porous screens in applications where the angle of incidence changes continuously across the face of the screen. New methods are introduced where the resistance of the screen is calculated as a function of the changing angle of incidence. The methods currently used are also investigated and compared with results from the new methods. Extensive experimental work was required to supply empirical data for the validation of the numerical methods that are proposed. For this reason, the first part of this study focused on the design construction and commissioning of a low speed wind tunnel. Results are presented and discussed for flow profiles through wide-angle diffusers at different angles and also for a number of different screens positioned in the centre of the diffuser. This study also investigates the sensitivity of a CFD simulation code to factors such as numerical discretisation schemes, turbulence models and solution relaxation specifically for wide-angle diffusers. These factors were tested for diffusers at different angles and included tests on open diffusers and also with screens positioned inside the diffuser. It was concluded that the current methods used are not adequate to capture the true flow profiles for a range of different screen geometries. Although the proposed models did improve on the limitations of the current methods, it was found that the applicability of these models is still limited and that further research would be required to develop numerical methods that are valid for a wide range of applications.
Thesis (M. Tech. Mechanical engineering -- Vaal University of Technology
Keywords: Emission legislation; Fossil fuel pollution; Ash filtering; Electrostatic precipitation; Atmospheric pollution; Electrostatic precipitators; Computational Fluid Dynamics; 628.53; Electrostatic precipitation; Dust -- Removal.; Electric power-plants -- Environmental aspects.